SISTEM PAKAR DIAGNOSA GEJALA KECANDUAN GAME ONLINE BERBASIS WEB MENGGUNAKAN METODE BACKWARD CHAINING - Shannon Marget Cloudy Silalahi (Fakultas Teknologi Informasi - Universitas Advent Indonesia, 2021)
Expert Systems are part of Artificial Intelligence, which contains the knowledge and experience provided by many experts according to certain areas of knowledge so that everyone can use to solve specific problems. The implementation of expert systems is widely used in the field of health such as psychological disorders such as addiction or addiction. For example, diagnosing a sign of addiction. Diagnosis is the process of examining something using certain methods and techniques. Diagnosis is done to explain whether someone issues / reports certain things such as psychological illness such as online game addiction It is expected that with this system, lay people can solve certain problems easily help experts in that field. Also provides convenience in diagnosing someone against online game addiction and provides convenience in the category information on online game addiction. While for experts, we can also use this system as an experienced assistant. This developed application aims to predict population growth rates by only analyzing the data with website-based. This method is the right method in the expert system.